2017
DOI: 10.1111/jgh.13633
|View full text |Cite
|
Sign up to set email alerts
|

Association of decreased expression of the macrophage scavenger receptor MARCO with tumor progression and poor prognosis in human hepatocellular carcinoma

Abstract: Our study is the first to demonstrate an association between MARCO expression and the progression and prognosis of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
22
2
Order By: Relevance
“…The literature to date on the prognostic significance of MARCO in cancer is sparse. Sun et al (22) reported that a decreased expression of MARCO was associated with tumor progression and poor prognosis in hepatocellular carcinoma and Lundgren et al (23) showed that high density of MARCO + TAMs in certain subtypes of periampullary pancreatic cancer predicted shorter survival. To the best of our knowledge, the expression and prognostic impact of MARCO in GE adenocarcinoma has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The literature to date on the prognostic significance of MARCO in cancer is sparse. Sun et al (22) reported that a decreased expression of MARCO was associated with tumor progression and poor prognosis in hepatocellular carcinoma and Lundgren et al (23) showed that high density of MARCO + TAMs in certain subtypes of periampullary pancreatic cancer predicted shorter survival. To the best of our knowledge, the expression and prognostic impact of MARCO in GE adenocarcinoma has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A similar mechanism of action, promoting the anti-tumoral functions of macrophages in tumors, has been observed for anti-MARCO mAbs, in murine models of breast, colon cancer, and melanoma [ 145 ]. These antibodies target the pattern-recognition scavenger receptor, MARCO, which is overexpressed in TAMs and linked to poor prognosis in breast, lung, and hepatic cancer [ 146 , 147 , 148 ]. Bispecific antibodies, targeting angiopoietin-2 (Ang-2) and vascular endothelial growth factor (VEGF), showed TAMs reprogramming and delayed tumor growth in glioma murine models [ 149 ].…”
Section: Monoclonal Antibodies To Reprogram Tamsmentioning
confidence: 99%
“…For example, Kupffer cells can be divided into two types, namely CD68+MARCO- (macrophage receptor with collagen structure) and CD68+MARCO+cells ( MacParland et al 2018 ). The up-regulation of Marco expression inhibits the migration and invasion of HCC cells, thereby alleviating tumor progress ( Sun et al, 2017 ). Furthermore, the massive infiltration of CD68+CD163+ macrophages and total CD68+ macrophages are related to the poor prognosis of HCC patients, while CD68+CD169+ macrophages and CD68+CD38+ macrophages are the opposite ( Lam et al, 2019 ; Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%